MATLAB-based modelling of Distribution STATCOM applied to isolated power system. (7th June 2006) - Singh, Bhim; Adya, Alka; Mittal, A.P.; Gupta, J.R.P.
This paper presents the modelling of Distribution Static Compensator (D-STATCOM) used in isolated power systems. The model of D-STATCOM is developed using Power System Block-set (PSB) and Simulink toolboxes of standard MATLAB software. Two proportional integral PI controllers are used to control DC bus voltage and AC bus voltage regulation at the point of common coupling. Results are presented for D-STATCOM used in an isolated distribution system fed from an alternator. It is observed from results that D-STATCOM is able to improve power factor, provide voltage regulation, balance the loads and reduce harmonics.